INFORMATION LITERACY, DISASTER FIQH, AND POLICY ADVOCACY: A STUDY OF NAHDLATUL ULAMA’S VISION IN NATIONAL DISASTER MITIGATION - Putri Alisia Silaen; Junaidi Junaidi; Mardian Idris (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2026)
Indonesia is a country with a highly critical vulnerability to natural disasters due to its geographical location andthe impacts of climate change. The involvement of non-state actors, such as Nahdlatul Ulama (NU), is crucial in driving responsive public policies through the articulation of Fiqh Bencana (Disaster Jurisprudence). This studyaims to analyze how NU’s theological vision on disasters is constructed and transformed into substantial political advocacy strategies, using a case study of the disaster management movement in North Sumatra in late 2025.Employing a qualitative method with in-depth interviews involving key figures from LBM-NU, LPBI-NU, Muslimat NU, GP Ansor, and the beneficiaries, this study finds that NU has successfully bridged "heavenly language" (theological ethics) and "bureaucratic language" (technocratic management) through a Civil Islam approach. The results indicate a synergistic division of roles among LBM-NU as the provider of macro-microlegal legitimacy, LPBI-NU as the tactical-institutional translator, Muslimat NU as the guardian of gender inclusivity, and GP Ansor (Bagana) as the field executors. The NU Peduli (NU Cares) movement during the disasters in late 2025 in North Sumatra serves as empirical evidence of this collaboration's effectiveness indismantling cultural fatalism and filling the gaps in the government's technocratic hegemony.